AUGUSTE BÉHAL - Jaime Wisniak (Revista CENIC Ciencias Químicas, 2022)
Auguste Béhal (1859-1941) was a French pharmacist that developed the chemistry of acetylene derivatives and studied the composition of vegetable creosotes, the decomposition of chloral, and the preparation and properties of asbolin. These studies led to the synthesis of a large number of new organic compounds, several of them with therapeutic value